The interaction between oxytocin receptor gene methylation and maternal behavior on children's early theory of mind abilities. (May 2020) - MacKinnon, Anna L.; Feeley, Nancy; Gold, Ian; Hayton, Barbara; King, Leonora; Nagy, Corina; Robins, Stephanie; Turecki, Gustavo; Zelkowitz, Phyllis
Abstract: Theory of mind, the ability to represent the mental states of others, is an important social cognitive process, which contributes to the development of social competence. Recent research suggests that interactions between gene and environmental factors, such as oxytocin receptor gene ( OXTR ) polymorphisms and maternal parenting behavior, may underlie individual differences in children's theory of mind. However, the potential influence of DNA methylation of OXTR remains unclear. The current study investigated the roles of OXTR methylation, maternal behavior, and their statistical interaction on toddlers' early emerging theory of mind abilities. Participants included a community sample of 189 dyads of mothers and their 2- to 3-year-old children, whose salivary DNA was analyzed. Results indicated that more maternal structuring behavior was associated with better performance, on a battery of three theory of mind tasks, while higher OXTR methylation within exon 3 was associated with poorer performance. A significant interaction also emerged, such that OXTR methylation was related to theory of mind among children whose mothers displayed less structuring, when controlling for children's age, sex, ethnicity, number of child-aged siblings, verbal ability, and maternal education. Maternal structuring behavior may buffer the potential negative impact of hypermethylation on OXTR gene expression and function.